FACTORS AFFECTING THE DEVELOPMENT OF AN INTEGRATED TOLL TRANSACTION SYSTEM TO IMPROVE TRAFFIC VOLUME DISTRIBUTION - Fitri Hidayati; Ayomi Dita Rarasati (Jurnal Pensil : Pendidikan Teknik Sipil, 2023)
The Indonesian government has attempted to reduce traffic congestion on toll roads by implementing a non-cash toll transaction system that has been valid on all Indonesian toll roads since October 2017. However, heavy traffic that causes traffic congestion on toll roads in urban areas often occurs. This study aimed to find out the factors that affect the development of the toll transaction system and the extent to which vehicles will be distributed through the preferences of road users to choose to enter the toll road or not. This research method used a quantitative descriptive approach with online and offline surveys through Stated Preference. Respondents were class I – V vehicle users who crossed Prof. Dr. Ir. Soedijatmo Toll Road with the direction of travel from the Jakarta Intra Urban Toll Road. The results of the study indicated that the implementation of contactless cashless toll transactions (Electronic Toll Collection (ETC)) can reduce the interest of road users to enter toll roads if fines are imposed, but on the other hand road users are still highly interested in entering toll road because there is a toll transaction time cut service. In the congestion pricing scenario, there was an increase in the distribution of traffic volume because the number of vehicles decreased along with the reduced interest of road users to enter the toll road due to the higher toll rate increase.